2022
DOI: 10.21037/atm-22-4389
|View full text |Cite
|
Sign up to set email alerts
|

FGF10 mediates protective anti-oxidative effects in particulate matter-induced lung injury through Nrf2 and NF-κB signaling

Abstract: Background: Particulate matter (PM), a well-known environmental pollutant, is an independent risk factor associated with the morbidity of various respiratory diseases. Oxidative stress is an important pathophysiological mechanism related to PM exposure, which mediates redox-sensitive inflammatory signaling, leading to lung injury. Fibroblast growth factor 10 (FGF10), a paracrine fibroblast growth factor that mediates mesenchymal to epithelial signaling, participates in epithelial repair during lung injury. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Tichelaar JW et al confirmed that FGF7 improved survival during ALI in adult mouse lungs after short-term expression [ 23 ]. Wang Q et al demonstrated that the anti-inflammatory effect of FGF10 on NF-κB signaling was mediated through the regulation of oxidative stress [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tichelaar JW et al confirmed that FGF7 improved survival during ALI in adult mouse lungs after short-term expression [ 23 ]. Wang Q et al demonstrated that the anti-inflammatory effect of FGF10 on NF-κB signaling was mediated through the regulation of oxidative stress [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…iii) Antioxidants based on endogenous molecules Fibroblast growth factor 10 (FGF10) is an endogenous paracrine signaling molecule that has a role in the maintenance of lung homeostasis, as well as epithelial regeneration and repair. Exogenous FGF10 has also demonstrated to protect against lung injury, and in vitro works on bronchial epithelial cells exposed to PM have confirmed that FGF10 triggered Nrf2 induction (Liu et al, 2022b), as well as NF-κB downregulation (Wang et al, 2022b), resulting in antioxidant and anti-inflammatory activities. The amino acid proline is yet another endogenous molecule that has recently been studied in the context of PM-induced oxidative stress, due to its inherent broad antioxidant profile.…”
Section: Compounds With Antioxidant Activity Against Pm-induced Oxida...mentioning
confidence: 94%
“…The participation of the nuclear factor erythroid 2-related factor 2 (Nrf2) in the oxidative stress triggered by PM has been extensively reported in recent years (Badran et al, 2020;Bagam et al, 2021;Housseiny et al, 2020;Ito et al, 2020;Liu et al, 2022b;Saha et al, 2022;Shi et al, 2023;Shrestha et al, 2021;Son et al, 2020;Tian et al, 2021;Wang et al, 2022aWang et al, , 2022bWang et al, , 2022cXue et al, 2021b). This is not surprising given the key role of Nrf2 in the protection against oxidative stimuli (Saha et al, 2020), acting as a sensor to protect the cells against oxidative damage induced by PM-generated ROS.…”
Section: Nrf2: the Master Regulator Of Antioxidant Responsementioning
confidence: 96%
See 1 more Smart Citation